Aircraft Industry Evacuation in 1941 - M Yu Mukhin (RUDN Journal of Russian History, 2012)
The article is devoted to the evacuation process of aircraft plants at the beginning of the Great Patriotic War. The author considers the issues of the prewar preparation of the evacuation process in general, the specific features of particularly aircraft industry evacuation, the course and results of the practical moves on transferring the production of aircraft industry to the eastern regions of the USSR.